Government expenditure components that affects economic growth in Malaysia / Ahmad Shah Fitri Mohammad - Mohammad, Ahmad Shah Fitri (Faculty of Business and Management, 2018)
The purpose of the study is to investigate the relationship between the government expenditure and the economic growth in Malaysia for period of 30 years from year 1987 to 2016. There were three government expenditure components had been listed which are Education Expenditure (EDU), Health Expenditure (HEA), Defense and Security Expenditure (DAS) as independent variables and Economic Growth (GDP) as dependent variable. This study used 30 years secondary data for each variable from year 1987 to 2016 on yearly basis. This study used Eviews9 software as a statistical tool for the data analysis. All the results obtained portrayed all the variables which are EDU, REA, and DAS towards GDP_ This study would be beneficial to the researcher, to the public. and policy makers for them to shape the future of a country without wasting any resources.